Economic costs in relation to clinical results of laparoscopic and open colon surgery in a health care center in the interior of the country. observational study and literature review - Medina Gallardo, Nolberto Adrián; Nieves Valverde, José Luis; Heguaburu Piquinela, Michel; Barrios Caro, Daniel Eduardo; Martin Egea, Miguel Ángel; Ihlenfeld Berretta, Juan (Cirugía del Uruguay, 2025)
2023 AWARD at the 73rd Uruguayan Congress of Surgery as BEST FREE WORK. Introduction: Laparoscopic colon surgery offers advantages in terms of fewer postoperative complications, shorter hospital stays and probably costs, according to several scientific studies. Objectives: To determine the differences in terms of clinical outcomes and overall costs of laparoscopic colon surgery compared to open surgery and to review the literature on the subject. Material and Methods: A retrospective observational descriptive study was carried out, through the review of medical records and cost analysis of patients operated on at CAMEC-IAMPP (Colonia Department, Uruguay) between January 2019 and July 2023. The groups were compared in clinical outcomes according to the rate of general complications, suture failures and mortality. In terms of costs, the cost of the surgical procedure, costs of the postoperative period and overall costs of the care process were compared. Results: A total of 197 records were obtained, of which 88 patients were analyzed according to the inclusion criteria. 71 patients (80.7%) underwent laparoscopic surgery and 17 (19.3%) underwent open surgery. The main indication was neoplastic disease, in 87.5% of the total sample. The average age was 66.1 years for the laparoscopic group and 76.0 for the open surgery group. The most frequent site of the pathology to be treated was the right colon for both groups (45.2% and 52.9% for laparoscopy and open surgery, respectively), followed by the sigmoid colon (40.8% and 35.3%). Overall mortality was 1.4% for the laparoscopic group and 17.0% for the open group, while suture failure rates were 12.7% and 17.0%. The average hospital stay was 8.35 days for laparoscopic surgery and 9.52 days for the open group. Regarding costs, although the average cost of the surgical procedure was higher in the laparoscopic group ($76,537.0 vs. $71,896.8), the overall costs were slightly favorable in these patients ($183,961.2 vs. $188,342.3), due to lower postoperative expenses ($107,424.2 vs. $116,445.5). Discussion and conclusions: In the sample studied, patients undergoing laparoscopic colectomy represented a lower cost of the care process in overall terms compared to the open approach, due to lower expenses in the postoperative period due to complications, in line with the available literature on the subject.